Endothelial cell-specific reduction of heparan sulfate suppresses glioma growth in mice - Takamasa Kinoshita (Springer, 2021)
Abstract Purpose Heparan sulfate (HS) is one of the factors that has been suggested to be associated with angiogenesis and invasion of glioblastoma (GBM), an aggressive and fast-growing brain tumor. However, it remains unclear how HS of endothelial cells is involved in angiogenesis in glioblastoma and its prognosis. Thus, we investigated the effect of endothelial cell HS on GBM development. Methods We generated endothelial cell-specific knockout of Ext1, a gene encoding a glycosyltransferase and essential for HS synthesis, and murine GL261 glioblastoma cells were orthotopically transplanted. Two weeks after transplantation, we examined the tumor progression and underlying mechanisms. Results The endothelial cell-specific Ext1 knockout (Ext1 CKO ) mice exhibited reduced HS expression specifically in the vascular endothelium of the brain capillaries compared with the control wild-type (WT) mice. GBM growth was significantly suppressed in Ext1 CKO mice compared with that in WT mice. After GBM transplantation, the survival rate was significantly higher in Ext1 CKO mice than in WT mice. We investigated how the effect of fibroblast growth factor 2 (FGF2), which is known as an angiogenesis-promoting factor, differs between Ext1 CKO and WT mice by using an in vivo Matrigel assay and demonstrated that endothelial cell-specific HS reduction attenuated the effect of FGF2 on angiogenesis. Conclusions HS reduction in the vascular endothelium of the brain suppressed GBM growth and neovascularization in mice.